2012
DOI: 10.1002/bbb.1342
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the transition to a next‐generation biofuels industry in the US Midwest

Abstract: Corn grain ethanol production is a mature industry built on a Midwestern agricultural infrastructure. Second‐ and third‐generation biofuels and bio‐based products industries could take advantage of this robust framework. Significant but not insurmountable barriers remain for grower acceptance of bioenergy crop plants and capital investment in transitioning from grain to lignocellulosic biomass at scale. The existing infrastructure in the Midwest provides a model for implementing an environmentally responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…[1][2][3][4][5] Multiple crops have been independently bred to store high concentrations of sucrose in terminal storage organs, namely, the taproots of sugar beet (Beta vulgaris L.), and the stems of sweet sorghum (Sorghum bicolor L. Moench) and sugarcane (Saccharum officinarum L.). [5][6][7][8][9] However, the sucrose contents of these crops appear to be approaching maximal levels attainable from breeding efforts 10,11 ; therefore, new approaches are needed to increase sucrose accumulation in storage organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Multiple crops have been independently bred to store high concentrations of sucrose in terminal storage organs, namely, the taproots of sugar beet (Beta vulgaris L.), and the stems of sweet sorghum (Sorghum bicolor L. Moench) and sugarcane (Saccharum officinarum L.). [5][6][7][8][9] However, the sucrose contents of these crops appear to be approaching maximal levels attainable from breeding efforts 10,11 ; therefore, new approaches are needed to increase sucrose accumulation in storage organs.…”
mentioning
confidence: 99%
“…3,4,[12][13][14][15][16] Different sorghum genotypes have been selectively bred to store carbohydrates in contrasting storage organs: sweet sorghums accumulate large quantities of soluble sugars, mostly sucrose, in stem tissues, whereas grain sorghums primarily store carbohydrates as starch in the seeds. 1,2,6,17,18 The molecular basis for the difference in carbohydrate partitioning between these sorghum types is unknown. Previous research found that sucrose accumulation within sweet sorghum stems was not correlated with the activities of enzymes involved in sucrose metabolism, invoking sucrose transport proteins as potentially controlling sucrose content.…”
mentioning
confidence: 99%
“…Because of the genetic colinearity of grasses (Devos, 2005), gene discovery in any one of them enables the rapid identification of putative orthologs in annual and perennial C4 energy grasses, such as Miscanthus spp., switchgrass, sorghum, and tropical varieties of maize (Carpita and McCann, 2008;Dweikat et al, 2012). The maize Intermated B73 3 Mo17 (IBM) population is an immortalized set of lines derived from two elite inbreds, B73 and Mo17, that underwent four rounds of intermating at the F2 stage to increase recombination and, thus, genetic resolution .…”
mentioning
confidence: 99%
“…1). Energy sorghum is a key crop for the Midwestern (USA) biofuels industry (Dweikat et al 2012), and the success of derived components is dependent on increasing biomass by relating plant genotypes to their phenotypes (Vega-Sánchez and Ronald 2010;Yano and Tuberosa 2009). High-throughput phenotyping technologies have been implemented for isolated growth chambers or greenhouses (Batz et al 2016); however, there is an emerging need for field-based platforms to measure large quantities of plants exposed to natural climates throughout a growing season (Fiorani and Tuberosa 2013;Furbank 2009).…”
Section: Introductionmentioning
confidence: 99%